Optical properties of 3d-ions in crystals: spectroscopy and crystal field analysis - Brik, Mikhail G.; Avram, Nicolae M. (Springer Berlin Heidelberg, 2013)
"Optical Properties of 3d-Ions in Crystals: Spectroscopy and Crystal Field Analysis" discusses spectral, vibronic and magnetic properties of 3d-ions in a wide range of crystals, used as active media for solid state lasers and potential candidates for this role. Crystal field calculations (including first-principles calculations of energy levels and absorption spectra) and their comparison with experimental spectra, the Jahn-Teller effect, analysis of vibronic spectra, materials science applications are systematically presented. The book is intended for researchers and graduate students in crystal spectroscopy, materials science and optical applications. Dr. N.M. Avram is an Emeritus Professor at the Physics Department, West University of Timisoara, Romania; Dr. M.G. Brik is a Professor at the Institute of Physics, University of Tartu, Estonia.